Elementary Teachers’ Perceptions of the Effect of Using Puppet Theater Strategy on the Development of Personal (Cognitive and Social) Aspects in Jordan - Al-adwan, Asma tayseer Mohammad (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify the perceptions of primary stage teachers for the effect of using the puppet theater strategy in developing personal aspects (cognitive, social) in Jordan. The study population consisted of all primary school teachers in the southern Shouna schools, and the whole community of (112) teachers was taken in the first semester 2019/2020, and the researcher used the descriptive method to suit the nature of the study and the results showed what Follows: - The perceptions of primary teachers of the impact of the use of the puppet theater strategy in the development of cognitive aspects were high and significantly. - The perceptions of primary school teachers of the impact of using the puppet theater strategy in the development of social aspects have been high and significantly. In the results, the researcher made several recommendations The most important of them are: - Carrying out many studies and researches in different academic stages. - Attention to using the puppet theater strategy in the curriculum. - Training teachers to use the puppet theater strategy.